New Cooperativism: A study of emerging producer organisations in India - Mathew Abraham (Copenhagen Business School (CBS), 2015)
A majority of the world's agricultural production takes place on small farms (less than 2 hectares). India has one of the smallest average farm sizes with over 68 per cent of its farms being marginal in size (below 1 hectare). Small farm production is constrained by challenges of accessing lumpy inputs of management and asset specific machinery, markets, credit, extension services and technology. Collective actions in the form of cooperatives in many parts of the world have played a vital role in overcoming these challenges and enabling agricultural growth. However, cooperatives in India have suffered from low participation, over-dependence on state assistance, poor management, political interference in their functioning and poor benefits to intended target groups. In recent years Producer Organisational Formats (POFs) such as Producer Companies (PCs), Joint Liability Groups (JLGs) and Farmers Federations (FFs) have emerged in an attempt to address some of these challenges faced by small producers. Although policy makers recognize this new cooperativism to have the potential to address small producer disadvantages, progress has been little in supporting or promoting POFs in India due to limited understanding of their functioning, impact and potential. This knowledge gap motivated this research. Using a conceptual framework grounded in institutional and collective action theories, this thesis examines (a) how POFs are structured on organisational, social and economic terms and (b) how resources are allocated and incentives aligned within these institutions. The thesis finds that the examined POFs are small, regionspecific collective actions, organised with the help of non-governmental organisations (NGOs) supported by the state. POFs relied on networks of social relationships, trust, norms and sometimes religious ideology to prevent collective action problems that hindered effective organisation. In economic terms, POFs helped improve market access and increased marketable agricultural surplus at the household level; yet, this surplus was not sufficient for households with marginal sized land to solely depend on farming as a livelihood activity. As for resource allocation and incentive alignment within POFs, the even distribution of collective goods to all members was a strong material incentive for participation. Social capital in the form of networks, norms and trust among members also incentivised participation. In sum the study finds that POFs have the potential to improve access to markets, credit, inputs and research and extension services, the lack of which has hindered small and marginal producer viability. In some cases social disadvantages of access arising from gender and caste were addressed through these organisations.
hdl:10398/9120
Keywords: 650